Development of plug in drive train system for hybrid electric motorcycle - Mustika Yasti, Yasril (2013)
This thesis writing discussed about the study of Development of Plug-in Drive Train System for Hybrid Electric Motorcycle. Generally, Plug-in hybrid electric vehicles (PHEVs) use batteries to power an electric motor and use another fuel, such as gasoline or diesel, to power an internal combustion engine. Beyond battery storage and motor power, parallel drivetrain configuration is used to combine the power from the electric motor and the engine, allow them to switching between the two based on the drive profile—this is called "blended mode" or "mixed mode." The major challenges in order to complete this project is to make sure drivetrain functions very well, smooth during switching between modes, thus not damaging the engine especially during blended mode. To face these challenges, it is important to develop drivetrain configuration, thus analyze its final velocity, power and torque required for each modes. A review of literature made on the hybrid drivetrain systems outlines four different modes, namely: Electric Motor (EM) mode, Internal Combustion Engine (ICE) mode, blended mode and idle mode. The configuration shows that each mode has its own functions and characteristics depends on speed demands and also needs at certain circumstances. Mechanical coupling used to connects the engine and the electric motor to the drive shafts, and before reach final drive, there will be continuous variable transmission (CVT) component, which act as main transmission instead of going through several gears to perform gear ratio change. As final outcome, drivetrain configuration that has been finalized will be used as a benchmark to develop prototype of plug-in hybrid drivetrain system, thus works well with chassis and control system.